Crafting in the World Materiality in the Making - Burke, Clare; Spencer-Wood, Suzanne M. (Springer International Publishing : Imprint: Springer, 2019)
This volume expands understandings of crafting practices, which in the past was the major relational interaction between the social agency of materials, technology, and people, in co-creating an emergent ever-changing world. The chapters discuss different ways that crafting in the present is useful in understanding crafting experiences and methods in the past, including experiments to reproduce ancient excavated objects, historical accounts of crafting methods and experiences, craft revivals, and teaching historical crafts at museums and schools. Crafting in the World is unique in the diversity of its theoretical and multidisciplinary approaches to researching crafting, not just as a set of techniques for producing functional objects, but as social practices and technical choices embodying cultural ideas, knowledge, and multiple interwoven social networks. Crafting expresses and constitutes mental schemas, identities, ideologies, and cultures. The multiple meanings and significances of crafting are explored from a great variety of disciplinary perspectives, including anthropology, archaeology, sociology, education, psychology, women's studies, and ethnic studies. This book provides a deep temporal range and a global geographical scope, with case studies ranging from Europe, Africa, and Asia to the Americas and a global internet website for selling home crafted items.